Basic leaf-cutting wreckers of cultivated cabbage in the Poltava region - Писаренко, В. М.; Пономаренко, С. В. (Scientific Progress & Innovations, 2012)
Production harvests of cultivated cabbage of high quality is impossible without timely application of measures on protecting of it from harmful insects. The question of study of specific composition and long-term seasonal dynamics of quantity of basic wreckers of cabbage is probed in Ukraine and Poltava region. In the conditions of the Poltava region among the specialized wreckers of cabbage the most widespread is cabbage owlet moth (Mamestra brassicae L.) cabbage diamond-back moth (Plutella maculipennis (Curt.) and cabbage white butterfly (Pieris brassicae L.).